Valve-regulated lead-acid battery
Patent Information
- Application Number
- JP2020197595
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2020-11-27
- Publication Date
- 2025-03-11
- Estimated Expiration
- 2040-11-27
AI Technical Summary
【0013】 ハイレート放電での容量維持率に優れた制御弁式鉛蓄電池を提供する。
Smart Images

Figure 0007643017000019 
Figure 0007643017000001 
Figure 0007643017000002
Abstract
Description
[Technical field]
[0001] The present invention relates to a valve regulated lead-acid battery. [Background technology]
[0002] Lead-acid batteries are used in various applications, including automotive and industrial use. Lead-acid batteries include a negative electrode plate, a positive electrode plate, a separator (or mat), and an electrolyte. Each electrode plate includes a current collector and an electrode material. In order to impart various functions, additives may be added to the components of the lead-acid battery.
[0003] Patent Document 1 describes a lead-acid battery having a configuration in which a negative electrode plate formed by filling a negative electrode current collector with a negative electrode active material and a positive electrode plate formed by filling a positive electrode current collector with a positive electrode active material are stacked with a separator between them, and the plate group is housed in a battery case together with an electrolyte, and the negative electrode active material contains flake graphite and a formaldehyde condensate of sodium salt of bisphenol A aminobenzenesulfonate represented by a predetermined chemical structural formula in the negative electrode active material, the molecular weight of the formaldehyde condensate of sodium salt of bisphenol A aminobenzenesulfonate is 15,000 to 20,000, the sulfur content in the compound is 6 to 10 mass%, and the average primary particle diameter of the flake graphite is 100 μm or more and 220 μm or less.
[0004] Patent Document 2 describes a method for producing an electrode for a lead-acid battery, which comprises the steps of filling a support with a kneaded active material in which a fluororesin dispersion is added and kneaded to form fluororesin fibers, and then infiltrating the electrode with an aqueous silicone emulsion and then drying the electrode.
[0005] Patent Document 3 describes a negative electrode plate for a lead-acid battery in which a paste-type active material containing a shrinkage inhibitor is filled into a current collector, the negative electrode plate for a lead-acid battery being characterized in that the shrinkage inhibitor is polyoxyperfluoroethylenephenylamine represented by a specific chemical formula, and the polyoxyperfluoroethylenephenylamine is contained in an amount of 0.005 to 3% by weight relative to the paste-type active material.
[0006] Patent Document 4 describes a separator for a lead-acid battery, which is made of a microporous sheet containing a heavy metal adsorbent made of a rare earth compound that has high heavy metal adsorption capacity in a neutral region and low heavy metal adsorption capacity in an acidic region, and is characterized in that the heavy metal adsorbent is unevenly distributed in the thickness direction of the sheet, forming a layer containing the heavy metal adsorbent and a layer substantially not containing the heavy metal adsorbent that extend in the horizontal direction of the sheet.
[0007] Patent Document 5 describes a valve-regulated lead-acid battery in which an electrode plate group having a separator interposed between positive and negative electrodes is housed in a battery case, and an electrolyte is held between the electrode plate group and the separator, the separator being a mixed mat of glass fiber and organic fiber, and the electrolyte being a silica sol with added silica.
[0008] Patent Document 6 describes a method for producing a valve-regulated lead-acid battery in which an electrode plate group including positive and negative electrode plates and a separator is placed in a battery case, the method comprising the steps of: preparing a positive electrode plate using lead powder and red lead having a red lead content of 20% by mass to 80% by mass as raw positive electrode active material materials; and placing the electrode plate group in the battery case so that a compressive force of 9.8 to 34.3 kPa is applied to the electrode plate group. [Prior art documents] [Patent documents]
[0009] [Patent Document 1] JP 2013-41848 A [Patent Document 2] Japanese Patent Application Publication No. 58-19863 [Patent Document 3] Japanese Patent Application Publication No. 9-147874 [Patent Document 4] JP 2007-311333 A [Patent Document 5] JP 2008-204638 A [Patent Document 6] JP 2009-123433 A Summary of the Invention [Problem to be solved by the invention]
[0010] The main lifespan mode of valve-regulated lead-acid batteries (VRLA) is loss of electrolyte. As the loss of electrolyte progresses, the AGM separator shrinks and the contact resistance between the plates and the AGM separator (or electrolyte) increases. In addition, the specific gravity of the electrolyte increases, making it easier for the grid corrosion of the positive electrode to progress. As a result, the internal resistance of the battery increases and the capacity retention rate during high-rate discharge decreases. [Means for solving the problem]
[0011] One aspect of the present invention provides a battery comprising an electrode plate group, an electrolyte, and a battery case that contains the electrode plate group and the electrolyte, the electrode plate group comprising positive electrode plates, negative electrode plates, and an AGM separator interposed between the positive electrode plates and the negative electrode plates, wherein a pressure applied to the electrode plate group in the battery case in a stacking direction of the positive electrode plates and the negative electrode plates is 10 kPa or more and 40 kPa or less, and the density of the AGM separator when a compressive force of 20 kPa is applied in a thickness direction is 0.14 g / cm 3 More than 0.20g / cm 3 The negative electrode plate includes a negative electrode material, the negative electrode material includes a polymer compound, and the polymer compound is measured using deuterated chloroform as a solvent. 1 The present invention relates to a valve-regulated lead-acid battery having a peak in the range of 3.2 ppm or more and 3.8 ppm or less in the chemical shift of the H-NMR spectrum.
[0012] Another aspect of the present invention provides a battery comprising an electrode plate group, an electrolyte, and a battery case that contains the electrode plate group and the electrolyte, the electrode plate group comprising positive electrode plates, negative electrode plates, and an AGM separator interposed between the positive electrode plates and the negative electrode plates, wherein a pressure applied to the electrode plate group in the battery case in a stacking direction of the positive electrode plates and the negative electrode plates is 10 kPa or more and 40 kPa or less, and the density of the AGM separator when a compressive force of 20 kPa is applied in a thickness direction is 0.14 g / cm 3 More than 0.20g / cm 3 The negative electrode plate includes a negative electrode material, the negative electrode material includes a polymer compound, and the polymer compound is an oxy-C 2-4 The present invention relates to a valve regulated lead-acid battery having a repeating structure of alkylene units. Effect of the Invention
[0013] Provided is a valve regulated lead-acid battery that has an excellent capacity retention rate during high-rate discharge. [Brief description of the drawings]
[0014] [Figure 1] 1 is a cross-sectional view showing a schematic structure of a valve-regulated lead-acid battery according to one embodiment. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0015] A valve regulated lead acid battery (VRLA) according to one embodiment of the present invention includes a plate assembly, an electrolyte, and a battery case for accommodating the plate assembly and the electrolyte. The plate assembly includes a positive electrode plate, a negative electrode plate, and an AGM (Absorbed Glass Mat) separator interposed between the positive electrode plate and the negative electrode plate. The AGM separator is a nonwoven fabric containing glass fibers.
[0016] The negative electrode plate includes a negative electrode material. The positive electrode plate includes a positive electrode material. The negative electrode material and the positive electrode material are usually held by a current collector. The electrode material is the electrode plate excluding the current collector. A member such as a mat or pasting paper may be attached to the electrode plate. Such a member (also called an attachment member) is used integrally with the electrode plate and is therefore included in the electrode plate. When the electrode plate includes an attachment member (such as a mat or pasting paper), the electrode material is the electrode material excluding the current collector and the attachment member.
[0017] The negative electrode material includes a polymer compound. The polymer compound is measured using deuterated chloroform as a solvent. 1 The polymer compound has a peak in the range of 3.2 ppm to 3.8 ppm in the chemical shift of the H-NMR spectrum. 2-4 The alkylene unit may have a repeating structure. In the above 1H-NMR spectrum, the peak appearing in the chemical shift range of 3.2 ppm to 3.8 ppm is an oxy C 2-4 It comes from an alkylene unit.
[0018] By including a polymer compound in the negative electrode material, it is possible to suppress the progression of loss of electrolyte, which is the main lifespan mode of VRLA. The reason why loss of electrolyte can be suppressed is thought to be as follows. First, the above-mentioned polymer compound is likely to have a linear structure, and the lead surface in the negative electrode material is thinly and widely covered with the polymer compound. The polymer compound included in the negative electrode material exists in the vicinity of the lead, so the oxy-C 2-4 It is believed that the alkylene unit exerts a high adsorption effect on lead. When a wide area of the lead surface is covered with the polymer compound, the hydrogen overvoltage increases, making it difficult for hydrogen to be generated during overcharging. This reduces loss of electrolyte. As described above, in order to effectively exert the effect of the polymer compound, it is important that the negative electrode material contains a polymer compound, regardless of whether or not the components of the lead-acid battery other than the negative electrode material contain a polymer compound.
[0019] On the other hand, some of the polymer compounds adsorbed on the lead surface are dissolved into the electrolyte due to the volume change of the negative electrode material accompanying charging and discharging and the external force accompanying the generation of hydrogen gas. The polymer compounds dissolved into the electrolyte move to the positive electrode plate and are oxidized and decomposed. This promotes self-discharge of the positive electrode plate, and increases the charging current during float charging. As a result, corrosion of the positive electrode plate (especially the positive electrode collector) progresses, the internal resistance of the battery increases, and the high-rate discharge capacity decreases. In other words, it was found that while the loss of electrolyte can be suppressed by including a polymer compound in the negative electrode material, corrosion of the positive electrode plate caused by the polymer compound occurs, which ultimately leads to a trade-off in which the capacity retention rate during high-rate discharge decreases.
[0020] In contrast, the pressure applied to the electrode plate group in the battery container in the stacking direction of the positive and negative plates (hereinafter also referred to as "compression") is set to 10 kPa or more and 40 kPa or less, and the density of the AGM separator when a compressive force of 20 kPa is applied in the thickness direction (hereinafter also referred to as "20 kPa density") is set to 0.14 g / cm 3 More than 0.20g / cm 3 When the content is set to be equal to or less than this range, even when a polymer compound is contained in the negative electrode material, a decrease in the capacity retention rate during high-rate discharge is suppressed.
[0021] First, by setting the pressure applied to the electrode group in the battery container within the above range, it is believed that the adhesive force of the polymer compound to the negative electrode material is improved, and the polymer compound is less likely to dissolve in the electrolyte. Second, by setting the pressure within the above range, the fluidity of the electrolyte is suppressed, the movement of the polymer compound dissolved in the electrolyte to the positive electrode plate is suppressed, and the polymer compound is less likely to be oxidized and decomposed at the positive electrode plate, and the self-discharge of the positive electrode is suppressed. Third, by making it difficult for the polymer compound to dissolve from the negative electrode plate, the effect of suppressing the loss of electrolyte is enhanced, the specific gravity of the electrolyte is less likely to increase, and the corrosion of the positive electrode plate is less likely to progress further.
[0022] When the pressure is 10 kPa or more, the polymer compound is less likely to dissolve into the electrolyte, and the effect of suppressing the loss of electrolyte is considered to be greater than when the pressure is less than 10 kPa. As a result, the increase in contact resistance between the electrode plate and the AGM separator is suppressed, particularly in VRLA. Furthermore, when the pressure is 10 kPa or more, the polymer compound is less likely to move to the positive electrode plate and is less likely to be oxidized and decomposed, and the progress of self-discharge of the positive electrode plate is also limited, compared to when the pressure is less than 10 kPa. Therefore, the charging current during float charging is less likely to increase, the progress of corrosion of the positive electrode plate (especially the positive electrode current collector) and the increase in the internal resistance of the battery are suppressed, and the capacity maintenance rate during high-rate discharge is improved. Furthermore, when the pressure is 40 kPa or less, free electrolyte that is not absorbed by the AGM separator is less likely to be generated, and the amount of electrolyte loss is suppressed. On the other hand, when the pressure is less than 10 kPa, the polymer compound is more likely to dissolve into the electrolyte, and the effect of suppressing the loss of electrolyte is also more likely to be reduced, compared to when the pressure is 10 kPa or more. In particular, in VRLA, the contact resistance between the plate and the AGM separator is likely to increase. Also, when the pressure is less than 10 kPa, the polymer compound is more likely to migrate to the positive plate and be oxidized and decomposed, compared to when the pressure is 10 kPa or more, and the self-discharge of the positive plate is more likely to progress. As a result, the charging current during float charging increases, and the corrosion of the positive plate (especially the positive electrode current collector) progresses, increasing the internal resistance of the battery and decreasing the capacity retention rate during high-rate discharge. Note that when the pressure exceeds 40 kPa, the amount of electrolyte loss increases slightly, but this is thought to be due to an increase in free electrolyte that is not absorbed by the AGM separator.
[0023] However, in order to suppress the migration of the eluted polymer compound to the positive plate, it is necessary to set the 20 kPa density of the AGM separator within the above range. When the density of the AGM separator is within the above range, the physical obstacle caused by the glass fibers constituting the AGM separator becomes large, the fluidity of the electrolyte decreases, and the flow path of the electrolyte moving from the surface of the negative plate to the surface of the positive plate through the AGM separator becomes longer. In addition, when the 20 kPa density of the AGM separator is within the above range, the distance between the glass fibers becomes shorter and the surface tension becomes larger. As a result, the electrolyte present between the glass fibers tends to remain there. Therefore, it is considered that the polymer compound eluted into the electrolyte becomes even more difficult to reach the positive plate.
[0024] The 20kPa density of the AGM separator is 0.14g / cm 3 In the above cases, the physical barrier of the glass fibers is sufficient, so the polymer compound is less likely to move to the positive electrode plate and is less likely to be oxidized and decomposed. This suppresses self-discharge of the positive electrode and improves the capacity retention rate during high-rate discharge. In addition, the 20 kPa density of the AGM separator is 0.20 g / cm 3 If the density is less than 0.14 g / cm, the free electrolyte is reduced, making it difficult to reduce the electrolyte, suppressing an increase in the specific gravity of the electrolyte, and suppressing corrosion of the positive electrode plate and an increase in the internal resistance of the battery. As a result, the capacity retention rate during high-rate discharge is improved. On the other hand, the 20 kPa density of the AGM separator is 0.14 g / cm 3 If the density is less than 0.20 g / cm, the physical barrier provided by the glass fibers is insufficient, and the polymer compound migrates to the positive plate and is easily decomposed by oxidation. This causes the self-discharge of the positive electrode to progress, and the capacity retention rate during high-rate discharge decreases. Also, the 20 kPa density of the AGM separator is 0.20 g / cm. 3 Above this level, the amount of free electrolyte increases, causing an increase in the amount of electrolyte loss, and the specific gravity of the electrolyte also increases. As a result, corrosion of the positive electrode plate progresses, the internal resistance of the battery increases, and the capacity retention rate during high-rate discharge decreases.
[0025] In this specification, the pressure applied to the plate group in the battery case, the 20 kPa density of the AGM separator, the organic fiber content in the AGM separator, and the polymer compound content in the negative electrode material are determined for the plate group, AGM separator, and negative plate removed from a fully charged lead-acid battery.
[0026] <Fully charged state> The fully charged state of a valve-regulated lead-acid battery is a state in which constant current and constant voltage charging of 2.23 V / cell is performed in an air tank at 25°C ± 2°C at a current (A) that is 0.2 times the value (unit: Ah) specified for the rated capacity, and charging is terminated when the charging current during constant voltage charging reaches a value (A) that is 0.005 times the value (unit: Ah) specified for the rated capacity. A fully charged lead-acid battery refers to a lead-acid battery that has already been formed and is fully charged. If the lead-acid battery is formed, it may be fully charged immediately after formation, or after some time has passed since formation (for example, a lead-acid battery that is in use (preferably in the early stages of use) after formation may be fully charged). An early stage battery refers to a battery that has not been used for a long time and has hardly deteriorated.
[0027] <Compression> The pressure applied to the plate group in the battery case can be measured by the following method. First, the plate group removed from the fully charged lead-acid battery is sandwiched between a pair of resin plates from both sides in the stacking direction of the positive and negative plates while still containing the electrolyte. Next, the plate group is compressed to the dimension D in the stacking direction of the cell chamber in the battery case that contained the plate group, and the pressure applied to the plate group at this time is measured as the pressure by a pressure sensor.
[0028] <Distance between poles G> In the plate assembly compressed in the stacking direction to the dimension D when measuring the compression, the distance between the positive plate and the negative plate (hereinafter referred to as the inter-electrode distance G) may be, for example, 1.0 mm or more, 1.5 mm or more, 2.0 mm or more, or 2.5 mm or more. However, from the viewpoint of suppressing the internal resistance of the battery, the inter-electrode distance G is preferably 2.5 mm or less. The inter-electrode distance can be calculated by measuring the thickness of the positive plate, the thickness of the negative plate, and the thickness of the AGM separator included in the compressed plate assembly at the center in the height direction, and then calculating the inter-electrode distance from the thicknesses and the number of plates and the dimension D of the cell chamber in the stacking direction.
[0029] <20kPa density> The 20 kPa density of an AGM separator can be measured according to 7.2.3 of SBA S 0406:2017 by the following method. First, the thickness of the AGM separator is measured. Specifically, the AGM separator is removed from a fully charged lead-acid battery, washed with water, and dried. After washing and drying, the AGM separator is cut into a size of 10 cm x 10 cm. Ten AGM separators of 10 cm x 10 cm size are stacked on the flat surface of a resin plate having flat surfaces on both sides, and the above resin plate is further stacked on top of them. Next, a 20 kg weight is placed on the resin plate, and a 20 kg / dm 2 A load of 1000 kgf / cm is applied. The total thickness of the 10 AGM separators is measured 30 seconds after the weight is placed. The thickness of each AGM separator is calculated as 1 / 10 of the total thickness of the 10 AGM separators. Next, the mass of the AGM separators is measured. Specifically, the mass of each of the 10 10 cm x 10 cm AGM separators produced above is measured and the average mass is calculated. The 20 kPa density (D) is then calculated from the thickness t (cm) of each AGM separator and the average mass W (g) of the AGM separators calculated above using the formula: D = W / (10 x 10 x t).
[0030] The thickness t of the AGM separator required above may be, for example, 0.15 cm (1.5 mm) or more, 0.20 cm (2.0 mm) or more, or 0.25 cm (2.5 mm) or more from the viewpoint of absorbing a sufficient amount of electrolyte. However, the thickness t of the AGM separator is preferably 0.30 cm (3.0) mm or less from the viewpoint of suppressing the internal resistance of the battery. The thickness t of the AGM separator is appropriately selected according to the interelectrode distance G, but is preferably larger than the interelectrode distance G. Specifically, the t / G ratio preferably satisfies 1.05≦t / G≦1.4, and may also satisfy 1.1≦t / G≦1.3.
[0031] When a lead-acid battery has two or more electrode plate groups, at least one of the electrode plate groups may satisfy the above conditions. However, it is preferable that 50% or more (more preferably 80% or more or 90% or more) of the number of electrode plate groups contained in the lead-acid battery satisfy the above conditions. The ratio of the electrode plate groups that satisfy the above conditions among the electrode plate groups contained in the lead-acid battery is 100% or less. It is preferable that all of the electrode plate groups contained in the lead-acid battery satisfy the above conditions.
[0032] Hereinafter, each of the main components of the lead-acid battery according to the embodiment of the present invention will be described, but the present invention is not limited to the following embodiment.
[0033] [Negative plate] A negative electrode plate usually includes a negative electrode current collector in addition to a negative electrode material. The negative electrode plate can be formed by coating or filling a negative electrode current collector with a negative electrode paste, aging and drying the negative electrode paste to produce an unformed negative electrode plate, and then forming the unformed negative electrode plate. The negative electrode paste is prepared, for example, by kneading lead powder, a polymer compound, other additives as necessary, water, and sulfuric acid (or an aqueous sulfuric acid solution). The unformed negative electrode plate may be aged at a temperature higher than room temperature and at a high humidity.
[0034] The formation can be carried out by immersing the plate group including the unformed negative plate in an electrolyte containing sulfuric acid in a lead-acid battery container and charging the plate group. However, the formation may be carried out before assembling the lead-acid battery or the plate group. The formation produces spongy lead.
[0035] (Negative electrode current collector) The negative electrode current collector may be formed by casting lead (Pb) or a lead alloy, or may be formed by processing a lead sheet or a lead alloy sheet. Examples of the processing method include expanding and punching. It is preferable to use a lattice-shaped current collector as the negative electrode current collector because it is easy to support the negative electrode material.
[0036] The lead alloy used for the negative electrode current collector may be any of Pb-Sb alloy, Pb-Ca alloy, and Pb-Ca-Sn alloy. These lead or lead alloys may further contain at least one selected from the group consisting of Ba, Ag, Al, Bi, As, Se, Cu, etc. as an additive element. The negative electrode current collector may have a surface layer. The surface layer and the inner layer of the negative electrode current collector may have different compositions. The surface layer may be formed on a part of the negative electrode current collector. The surface layer may be formed on the ear of the negative electrode current collector. The surface layer of the ear may contain Sn or an Sn alloy.
[0037] (Negative electrode material) The negative electrode material includes a negative electrode active material (specifically, lead or lead sulfate) that exhibits capacity through an oxidation-reduction reaction, and a polymer compound. The negative electrode material may further include an additive. Examples of the additive include, but are not limited to, an organic shrinkage inhibitor, a carbonaceous material, and barium sulfate. The negative electrode active material in a charged state is spongy lead.
[0038] (Polymer Compound) The polymer compound satisfies at least one of the following conditions (i) and (ii). Condition (i) The polymer compound has a peak in the chemical shift range of 3.2 ppm to 3.8 ppm in the 1H-NMR spectrum measured using deuterated chloroform as a solvent. Condition (ii) The polymer compound is OxyC 2-4 Contains repeating alkylene units. OxyC 2-4 An alkylene unit is -O-R1- (R1 is C 2-4 It is a unit represented by the formula:
[0039] Under condition (i), the peak between 3.2 ppm and 3.8 ppm is oxy-C 2-4 It is derived from an alkylene unit. In other words, a polymer compound satisfying condition (ii) is also a polymer compound satisfying condition (i). However, a polymer compound satisfying condition (i) is not a polymer compound containing an oxy C 2-4 The polymer compound may contain a repeating structure of a monomer unit other than an alkylene unit, and may have a certain degree of molecular weight. The polymer compound satisfying the above (i) or (ii) may have a number average molecular weight (Mn) of, for example, 300 or more.
[0040] The polymeric compounds may include oxygen atoms bonded to end groups and -CH2- and / or -CH< groups bonded to the oxygen atoms. 1 In the H-NMR spectrum, the ratio of the integral value of the peak between 3.2 ppm and 3.8 ppm to the total integral value of this peak, the integral value of the peak of the hydrogen atom of the -CH2- group bonded to the oxygen atom, and the integral value of the peak of the hydrogen atom of the -CH< group bonded to the oxygen atom is, for example, 50% or more, or may be 80% or more, 85% or more, or may be 90% or more. 2-4It contains many alkylene units in the molecule. Therefore, it is considered that the polymer compound is more likely to have a linear structure and to easily cover the lead surface thinly. Therefore, it is possible to more effectively reduce the loss of liquid. In addition, since the lead surface is thinly covered, the charge acceptance is less likely to decrease and lead sulfate is less likely to accumulate, so that the increase in resistance during discharge is suppressed. Therefore, it is easier to ensure the capacity maintenance rate during high-rate discharge. For example, when a polymer compound has an -OH group at the end and a -CH2- group or -CH< group bonded to the oxygen atom of this -OH group, in the 1H-NMR spectrum, the peak of the hydrogen atom of the -CH2- group or -CH< group has a chemical shift in the range of more than 3.8 ppm to 4.0 ppm.
[0041] The polymer compound is OxyC 2-4 It is preferable that the alkylene unit contains a repeating structure. 2-4 When a polymer compound containing a repeating structure of alkylene units is used, it is believed that the polymer compound is more easily adsorbed to lead and that the polymer compound is more likely to have a linear structure, which makes it easier to thinly cover the lead surface. 2-4 It may contain an alkylene unit, and two or more kinds of oxy C 2-4 It may contain an alkylene unit. 2-4 Polymer compounds having a repeating structure of alkylene units also include those classified as surfactants (for example, nonionic surfactants).
[0042] Oxy C 2-4 Examples of the alkylene unit include an oxyethylene unit, an oxypropylene unit, an oxytrimethylene unit, an oxy2-methyl-1,3-propylene unit, an oxy1,4-butylene unit, and an oxy1,3-butylene unit. 2-4 The alkylene unit may have one type or two or more types.
[0043] Oxy C 2-4The alkylene unit may be, for example, an oxypropylene unit (-O-CH(-CH3)-CH2-). That is, the polymer compound may contain a repeating structure of oxypropylene units. Such a polymer compound has high adsorption properties for lead, but does not excessively adhere to the lead surface. Therefore, it is possible to effectively reduce loss of the electrolyte, and the charge acceptance is not likely to decrease and lead sulfate is not likely to accumulate, so that the increase in resistance during discharge is easily suppressed.
[0044] Oxy C 2-4 The alkylene unit may be, for example, an oxyethylene unit (-O-CH2-CH2-). That is, the polymer compound may contain a repeating structure of an oxyethylene unit. The repeating structure of an oxyethylene unit has high hydrophilicity, and therefore can selectively adsorb lead. This makes it easier to control the adsorption of the polymer compound to lead.
[0045] The polymer compound is OxyC 2-4 The hydroxy compound may contain at least one selected from the group consisting of a hydroxy compound having a repeating alkylene unit structure (hereinafter also referred to as hydroxy compound C), an etherified product of hydroxy compound C, and an esterified product of hydroxy compound C.
[0046] Here, the hydroxy compound C is polyC 2-4 Alkylene glycol, oxy C 2-4 PolyC, a copolymer and polyol containing repeating alkylene units 2-4 The polymer compound may be at least one selected from the group consisting of alkylene oxide adducts. When such a polymer compound is used, the liquid reduction can be more effectively suppressed.
[0047] Oxy C 2-4 Copolymers containing repeating alkylene units include different oxy C 2-4 Copolymers containing alkylene units, polyC 2-4 Alkylene glycol alkyl ether, poly C carboxylic acid2-4 Alkylene glycol ester, etc. The copolymer may be a block copolymer.
[0048] Polyol Poly C 2-4 Examples of polyols constituting the alkylene oxide adduct include aliphatic polyols, alicyclic polyols, aromatic polyols, and heterocyclic polyols. In terms of the ease with which the polymer compound spreads thinly over the lead surface, aliphatic polyols and alicyclic polyols (e.g., polyhydroxycyclohexane, polyhydroxynorbornane, etc.) are preferred, and among these, aliphatic polyols are preferred. Examples of aliphatic polyols include aliphatic diols and polyols with triols or more (e.g., glycerin, trimethylolpropane, pentaerythritol, sugars or sugar alcohols, etc.). Examples of aliphatic diols include alkylene glycols with 5 or more carbon atoms. Examples of alkylene glycols include C 5-14 Alkylene glycol or C 5-10 It may be an alkylene glycol. Examples of the sugar or sugar alcohol include sucrose, erythritol, xylitol, mannitol, sorbitol, etc. The sugar or sugar alcohol may have either a chain structure or a cyclic structure.
[0049] In the polyalkylene oxide adduct of polyol, the alkylene oxide is the oxy-C of the polymer compound. 2-4 Corresponding to an alkylene unit, at least C 2-4 In view of the ease with which the polymer compound has a linear structure, the polyol is preferably a diol.
[0050] The etherified product of the hydroxy compound C has -OR2 groups in which at least some of the terminal -OH groups of the hydroxy compound C (-OH groups consisting of a hydrogen atom of the terminal group and an oxygen atom bonded to this hydrogen atom) have been etherified (wherein R2 is an organic group). Of the terminals of the polymer compound, some terminals may be etherified, or all terminals may be etherified. For example, one terminal of the main chain of a linear polymer compound may be an -OH group, and the other terminal may be an -OR2 group.
[0051] The ester of the hydroxy compound C has an -OC(=O)-R3 group in which at least some of the terminal -OH groups of the hydroxy compound C are esterified (wherein R3 is an organic group). Some or all of the terminals of the polymer compound may be esterified. For example, one terminal of the main chain of a linear polymer compound may be an -OH group and the other terminal may be an -OC(=O)-R3 group.
[0052] Examples of the organic groups R2 and R3 include hydrocarbon groups. The hydrocarbon groups may have a substituent (such as a hydroxy group, an alkoxy group, or a carboxy group). The hydrocarbon groups may be aliphatic, alicyclic, or aromatic. The aromatic hydrocarbon groups and alicyclic hydrocarbon groups may have an aliphatic hydrocarbon group (such as an alkyl group, an alkenyl group, or an alkynyl group) as a substituent. The number of carbon atoms in the aliphatic hydrocarbon group as a substituent may be, for example, 1 to 30, 1 to 20, 1 to 10, 1 to 6, or 1 to 4.
[0053] Examples of the aromatic hydrocarbon group include aromatic hydrocarbon groups having 6 to 24 carbon atoms. The number of carbon atoms in the aromatic hydrocarbon group may be 20 or less, 14 or less, or 12 or less. Examples of the aromatic hydrocarbon group include aryl groups and bisaryl groups. Examples of the aryl group include phenyl groups and naphthyl groups. Examples of the bisaryl group include monovalent groups corresponding to bisarenes. Examples of bisarenes include biphenyl, bisarylalkanes (e.g., bisC6-10 Aryl C 1-4 Alkanes (such as 2,2-bisphenylpropane, etc.) are examples.
[0054] Examples of the alicyclic hydrocarbon group include alicyclic hydrocarbon groups having 16 or less carbon atoms. The alicyclic hydrocarbon group may be a cross-linked cyclic hydrocarbon group. The number of carbon atoms in the alicyclic hydrocarbon group may be 10 or less or 8 or less. The number of carbon atoms in the alicyclic hydrocarbon group may be, for example, 5 or more, or 6 or more.
[0055] Examples of alicyclic hydrocarbon groups include cycloalkyl groups (cyclopentyl, cyclohexyl, cyclooctyl, etc.), cycloalkenyl groups (cyclohexenyl, cyclooctenyl, etc.), etc. Alicyclic hydrocarbon groups also include hydrogenated aromatic hydrocarbon groups.
[0056] From the viewpoint of facilitating thin adhesion of the polymer compound to the lead surface, among the hydrocarbon groups, an aliphatic hydrocarbon group is preferred. The aliphatic hydrocarbon group may be saturated or unsaturated. Examples of the aliphatic hydrocarbon group include an alkyl group, an alkenyl group, an alkynyl group, a dienyl group having two carbon-carbon double bonds, and a trienyl group having three carbon-carbon double bonds. The aliphatic hydrocarbon group may be either linear or branched.
[0057] The number of carbon atoms in the aliphatic hydrocarbon group is, for example, 30 or less, and may be 26 or less or 22 or less, 20 or less or 16 or less, 14 or less or 10 or less, or 8 or less or 6 or less. The lower limit of the number of carbon atoms depends on the type of the aliphatic hydrocarbon group, and is 1 or more for alkyl groups, 2 or more for alkenyl groups and alkynyl groups, 3 or more for dienyl groups, and 4 or more for trienyl groups. Among these, alkyl groups and alkenyl groups are preferred because they facilitate thin adhesion of the polymer compound to the lead surface.
[0058] Specific examples of alkyl groups include methyl, ethyl, n-propyl, i-propyl, n-butyl, i-butyl, s-butyl, t-butyl, n-pentyl, neopentyl, i-pentyl, s-pentyl, 3-pentyl, t-pentyl, n-hexyl, 2-ethylhexyl, n-octyl, n-nonyl, n-decyl, i-decyl, undecyl, lauryl (dodecyl), tridecyl, myristyl, pentadecyl, cetyl, heptadecyl, stearyl, icosyl, henicosyl, and behenyl.
[0059] Specific examples of the alkenyl group include vinyl, 1-propenyl, allyl, cis-9-heptadecen-1-yl, palmitoleyl, and oleyl. The alkenyl group is, for example, 2-30 Alkenyl group or C 2-26 It may be an alkenyl group, C 2-22 Alkenyl group or C 2-20 It may be an alkenyl group, C 10-20 It may be an alkenyl group.
[0060] Among the polymer compounds, at least one selected from the group consisting of ethers of hydroxy compounds C and esters of hydroxy compounds C is preferred, and these polymer compounds preferably have a repeating structure of oxypropylene units or a repeating structure of oxyethylene units.
[0061] The polymer compound may have one or more hydrophobic groups. Examples of the hydrophobic group include, among the hydrocarbon groups exemplified as the organic group R2 or R3, aromatic hydrocarbon groups, alicyclic hydrocarbon groups, and long-chain aliphatic hydrocarbon groups. At least one of the hydrophobic groups may be a long-chain aliphatic hydrocarbon group having 8 or more carbon atoms. The action of such a hydrophobic group suppresses excessive coating of the polymer compound on the lead surface. The balance between the hydrophobic group and the hydrophilic group can control the balance between suppression of loss of the electrolyte and resistance during discharge.
[0062] The long-chain aliphatic hydrocarbon group may be an alkyl group, an alkenyl group, or the like, having 8 or more carbon atoms, preferably 12 or more, and more preferably 16 or more. A polymer compound having a long-chain aliphatic hydrocarbon group is less likely to cause excessive adsorption to lead, is less likely to reduce charge acceptance, and is less likely to accumulate lead sulfate, so that the effect of suppressing an increase in resistance during discharge is further enhanced. At least one of the hydrophobic groups may be a long-chain aliphatic hydrocarbon group. The carbon number of the long-chain aliphatic hydrocarbon group may be 30 or less, 26 or less, or 22 or less.
[0063] A polymer compound having a hydrophilic group and a hydrophobic group corresponds to a nonionic surfactant. The hydrophilic group may be a repeating structure of an oxyethylene unit. The repeating structure of an oxyethylene unit has high hydrophilicity. By the balance between the hydrophobic group and the repeating structure of an oxyethylene unit, it is possible to selectively adsorb to lead while suppressing excessive covering of the lead surface. Examples of polymer compounds corresponding to such nonionic surfactants include polyoxypropylene-polyoxyethylene block copolymers, etherified products of hydroxy compounds having a repeating structure of an oxyethylene unit, and esterified products of hydroxy compounds having a repeating structure of an oxyethylene unit. These can ensure high adsorption to lead even if they have a relatively low molecular weight (for example, Mn is 300 or more or 400 or more and 1000 or less). In polyoxypropylene-polyoxyethylene block copolymers, the repeating structure of an oxyethylene unit corresponds to a hydrophilic group, and the repeating structure of an oxypropylene unit corresponds to a hydrophobic group.
[0064] As the polymer compound corresponding to the nonionic surfactant, etherified products of polyethylene glycol (such as alkyl ethers), esterified products of polyethylene glycol (such as carboxylic acid esters), etherified products of the polyethylene oxide adducts of the above polyols (such as alkyl ethers), esterified products of the polyethylene oxide adducts of the above polyols (such as carboxylic acid esters), etc. may be used. More specific examples include polyethylene glycol oleate, polyethylene glycol dioleate, polyethylene glycol dilaurate, polyethylene glycol distearate, polyoxyethylene coconut oil fatty acid sorbitan, polyoxyethylene sorbitan oleate, polyoxyethylene sorbitan stearate, polyoxyethylene lauryl ether, polyoxyethylene tetradecyl ether, polyoxyethylene cetyl ether, etc., but are not limited thereto.
[0065] The HLB of the polymer compound classified as a surfactant is preferably 4 or more, more preferably 4.3 or more, from the viewpoint of further reducing the loss of the electrolyte solution. From the viewpoint of suppressing the increase in resistance during discharge, the HLB of the polymer compound is preferably 18 or less, more preferably 10 or less or 9 or less, and even more preferably 8.5 or less.
[0066] Oxy C 2-4 It is also preferable that the repeating structure of alkylene contains at least a repeating structure of an oxypropylene unit. A polymer compound containing an oxypropylene unit has peaks derived from -CH< and -CH2- of the oxypropylene unit in the chemical shift range of 3.2 ppm to 3.8 ppm in the 1H-NMR spectrum. Since the electron density around the atomic nuclei of the hydrogen atoms in these groups is different, the peaks are in a split state. Such a polymer compound has 1In the chemical shift of the H-NMR spectrum, for example, there are peaks in the range of 3.2 ppm to 3.42 ppm and in the range of more than 3.42 ppm to 3.8 ppm. The peaks in the range of 3.2 ppm to 3.42 ppm are derived from -CH2-, and the peaks in the range of more than 3.42 ppm to 3.8 ppm are derived from -CH< and -CH2-.
[0067] Examples of polymer compounds containing a repeating structure of oxypropylene units include polypropylene glycol, copolymers containing a repeating structure of oxypropylene units, polypropylene oxide adducts of the above polyols, and etherified or esterified products thereof. Examples of copolymers include oxypropylene-oxyalkylene copolymers (wherein the oxyalkylene is a C alkylene other than oxypropylene). 2-4 Examples of the oxypropylene-oxyalkylene copolymer include oxypropylene-oxyethylene copolymer and oxypropylene-oxytrimethylene copolymer. The oxypropylene-oxyalkylene copolymer may be called polyoxypropylene-polyoxyalkylene copolymer (for example, polyoxypropylene-polyoxyethylene copolymer). The oxypropylene-oxyalkylene copolymer may be a block copolymer (for example, polyoxypropylene-polyoxyethylene block copolymer). Examples of the etherified product include polypropylene glycol alkyl ether and alkyl ether of oxypropylene-oxyalkylene copolymer (alkyl ether of polyoxypropylene-polyoxyethylene copolymer, etc.). Examples of the esterified product include polypropylene glycol ester of carboxylic acid and carboxylic acid ester of oxypropylene-oxyalkylene copolymer (carboxylic acid ester of polyoxypropylene-polyoxyethylene copolymer, etc.).
[0068] Examples of polymer compounds containing a repeating structure of oxypropylene units include, but are not limited to, polypropylene glycol, polyoxypropylene-polyoxyethylene copolymers (such as polyoxypropylene-polyoxyethylene block copolymers), polyoxyethylene-polyoxypropylene alkyl ethers (such as alkyl ethers (butyl ethers) in which the above R2 is an alkyl having 10 or less carbon atoms (or 8 or less or 6 or less)), polypropylene glycol carboxylates (such as polypropylene glycol acetates in which the above R3 is an alkyl having 10 or less carbon atoms (or 8 or less or 6 or less)), and polypropylene oxide adducts of triol or higher polyols (such as polypropylene oxide adducts of glycerin).
[0069] In the polymer compound, the proportion of the oxypropylene unit is, for example, 5 mol% or more, and may be 10 mol% or more or 20 mol% or more. The proportion of the oxypropylene unit is, for example, 100 mol% or less. In the copolymer, the proportion of the oxypropylene unit may be 90 mol% or less, 75 mol% or less, or 60 mol% or less.
[0070] From the viewpoint of suppressing an increase in resistance during discharge, the content of the polymer compound in the negative electrode material is preferably 500 ppm or less by mass, and from the viewpoint of further suppressing loss of liquid, the content of the polymer compound in the negative electrode material is preferably 30 ppm or more by mass.
[0071] The content (by mass) of the polymer compound in the negative electrode material may be 30 ppm or more and 500 ppm or less, 30 ppm or more and 400 ppm or less, 30 ppm or more and 200 ppm or less, 50 ppm or more and 500 ppm or less, 50 ppm or more and 400 ppm or less, 50 ppm or more and 200 ppm or less, 80 ppm or more and 500 ppm or less, 80 ppm or more and 400 ppm or less, or 80 ppm or more and 200 ppm or less.
[0072] The polymer compound preferably contains a compound having a number average molecular weight (Mn) of 10,000 or less. In this case, the thickness of the coating of the polymer compound covering the surfaces of the lead and lead sulfate can be further reduced. As a result, the charge acceptance is less likely to decrease and lead sulfate is less likely to accumulate, so that the increase in resistance during discharge is further suppressed.
[0073] The polymer compound preferably contains a polymer compound with Mn of 500 or more. In this case, higher adsorption to lead can be ensured, and the lead surface can be easily covered with the polymer compound. The amount of overcharge electricity can be further reduced. Therefore, the effect of suppressing the progress of the reduction in the electrolyte can be enhanced.
[0074] The negative electrode material may contain one or more polymer compounds. The negative electrode material may use two or more polymer compounds having different Mn. In other words, the molecular weight distribution of the polymer compound may have multiple Mn peaks.
[0075] The Mn of the polymer compound may be 500 or more (or 1000 or more) and 10,000 or less, 500 or more (or 1000 or more) and 5,000 or less, 500 or more (or 1000 or more) and 4,000 or less, 500 or more (or 1000 or more) and 3,000 or less, or 500 or more (or 1000 or more) and 2,500 or less.
[0076] <Number average molecular weight> The number average molecular weight (Mn) is determined by gel permeation chromatography (GPC). The standard substance used in determining Mn is polyethylene glycol.
[0077] (Organic shrink-proofing agent) The organic shrinkage inhibitor is an organic compound that inhibits the shrinkage of lead, which is the negative electrode active material, when the lead-acid battery is repeatedly charged and discharged. As the organic shrinkage inhibitor, for example, at least one selected from the group consisting of lignin compounds and synthetic organic shrinkage inhibitors may be used.
[0078] Examples of the lignin compound include lignin and lignin derivatives. Examples of the lignin derivatives include lignin sulfonic acid or salts thereof (alkali metal salts (sodium salts, etc.)).
[0079] The synthetic organic shrinkage inhibitor used in lead-acid batteries is usually an organic condensation product (hereinafter, simply referred to as a condensation product). A condensation product is a synthetic product that can be obtained by utilizing a condensation reaction. The condensation product may contain an aromatic compound unit (hereinafter, also referred to as an aromatic compound unit). The aromatic compound unit refers to a unit derived from an aromatic compound incorporated in the condensation product. In other words, the aromatic compound unit is a residue of an aromatic compound. The condensation product may contain one type of aromatic compound unit, or may contain two or more types of aromatic compound units.
[0080] The condensate may be, for example, a condensate of an aromatic compound with an aldehyde compound. Such a condensate may be synthesized by reacting an aromatic compound with an aldehyde compound. Here, a condensate containing a sulfur element may be obtained by carrying out the reaction of an aromatic compound with an aldehyde compound in the presence of a sulfite, or by using an aromatic compound containing a sulfur element (e.g., bisphenol S) as an aromatic compound. For example, the sulfur element content in the condensate may be adjusted by adjusting at least one of the amount of sulfite and the amount of the aromatic compound containing a sulfur element. This method may be followed when using other raw materials. The aromatic compound to be condensed to obtain the condensate may be one type or two or more types. The aldehyde compound may be an aldehyde (e.g., formaldehyde), or may be a condensate (or polymer) of an aldehyde. Examples of the aldehyde condensate (or polymer) include paraformaldehyde, trioxane, and tetraoxymethylene. The aldehyde compound may be used alone or in combination of two or more types. From the viewpoint of high reactivity with aromatic compounds, formaldehyde is preferred.
[0081] The aromatic compound may have a sulfur-containing group. That is, the condensate may be an organic polymer containing a plurality of aromatic rings in the molecule and containing elemental sulfur as a sulfur-containing group. The sulfur-containing group may be directly bonded to the aromatic ring of the aromatic compound, or may be bonded to the aromatic ring as an alkyl chain having a sulfur-containing group, for example. Among the sulfur-containing groups, a sulfonic acid group or a sulfonyl group, which is a stable form, is preferred. The sulfonic acid group may exist in an acid form or in a salt form such as a Na salt.
[0082] Examples of the aromatic rings that aromatic compounds have include benzene rings and naphthalene rings. When an aromatic compound has multiple aromatic rings, the multiple aromatic rings may be linked by direct bonds or linking groups (e.g., alkylene groups (including alkylidene groups), sulfone groups) and the like. Examples of such structures include bisarene structures (biphenyl, bisphenylalkane, bisphenylsulfone, etc.).
[0083] Examples of aromatic compounds include compounds having the above aromatic ring and a functional group (such as a hydroxy group or an amino group). The functional group may be directly bonded to the aromatic ring, or may be bonded as an alkyl chain having a functional group. The hydroxy group also includes a salt of the hydroxy group (-OMe). The amino group also includes a salt of the amino group (a salt with an anion). Examples of Me include alkali metals (Li, K, Na, etc.) and metals of Group 2 of the periodic table (Ca, Mg, etc.). The aromatic compound may have a sulfur-containing group and a substituent other than the above functional group (such as an alkyl group or an alkoxy group) on the aromatic ring.
[0084] The aromatic compound that is the source of the aromatic compound unit may be at least one selected from the group consisting of bisarene compounds and monocyclic aromatic compounds.
[0085] Examples of the bisarene compound include a bisphenol compound, a hydroxybiphenyl compound, and a bisarene compound having an amino group (such as a bisarylalkane compound having an amino group, a bisarylsulfone compound having an amino group, and a biphenyl compound having an amino group). Among these, a bisphenol compound is preferable.
[0086] The bisphenol compound is preferably bisphenol A, bisphenol S, bisphenol F, or the like. For example, the bisphenol compound may contain at least one selected from the group consisting of bisphenol A and bisphenol S. By using bisphenol A or bisphenol S, an excellent shrinkage prevention effect on the negative electrode material can be obtained.
[0087] The bisphenol compound may have a bisphenol skeleton, and the bisphenol skeleton may have a substituent. That is, bisphenol A may have a bisphenol A skeleton, and the skeleton may have a substituent. Bisphenol S may have a bisphenol S skeleton, and the skeleton may have a substituent.
[0088] Preferred monocyclic aromatic compounds include hydroxymonoarene compounds and aminomonoarene compounds, and among these, hydroxymonoarene compounds are preferred.
[0089] Examples of the hydroxymonoarene compound include a hydroxynaphthalene compound and a phenol compound. For example, it is preferable to use a phenolsulfonic acid compound (phenolsulfonic acid or a substituted compound thereof) which is a phenol compound. As mentioned above, the phenolic hydroxy group also includes a salt of the phenolic hydroxy group (-OMe).
[0090] Examples of the aminomonoarene compounds include aminonaphthalene compounds and aniline compounds (such as aminobenzenesulfonic acid and alkylaminobenzenesulfonic acid).
[0091] The content of the organic shrinkage inhibitor in the negative electrode material is preferably, for example, 0.005% by mass or more, while from the viewpoint of suppressing a decrease in charge acceptance, the content of the organic shrinkage inhibitor in the negative electrode material is preferably 0.3% by mass or less.
[0092] (carbonaceous material) Carbon black, graphite, hard carbon, soft carbon, etc. can be used as the carbonaceous material contained in the negative electrode material. Examples of carbon black include acetylene black, furnace black, lamp black, etc. Furnace black also includes Ketjen Black (trade name). Graphite may be any carbonaceous material containing a graphite-type crystal structure, and may be either artificial graphite or natural graphite. The negative electrode material may contain one type of carbonaceous material, or may contain two or more types.
[0093] The content of the carbonaceous material in the negative electrode material is, for example, 0.05 mass% or more, and may be 0.10 mass% or more.The content of the carbonaceous material is, for example, 5 mass% or less, and may be 3 mass% or less.
[0094] (Barium Sulfate) The content of barium sulfate in the negative electrode material may be from 0.05 to 3% by mass, from 0.05 to 2% by mass, from 0.10 to 3% by mass, or from 0.10 to 2% by mass.
[0095] ≪Analysis≫ The method of analyzing the polymer compound and additives contained in the negative electrode material is described below. Prior to measurement or analysis, a fully charged lead-acid battery is disassembled to obtain a negative electrode plate to be analyzed. The obtained negative electrode plate is washed with water to remove sulfuric acid from the negative electrode plate. The washing is performed by pressing a pH test paper against the washed surface of the negative electrode plate until it is confirmed that the color of the test paper does not change. However, the washing time is within 2 hours. The washed negative electrode plate is dried at 60±5°C for about 6 hours in a reduced pressure environment. If the negative electrode plate contains an attachment material, the attachment material is removed as necessary. Next, a sample (hereinafter referred to as sample A) is obtained by separating the negative electrode material from the negative electrode plate. Sample A is crushed as necessary and subjected to analysis.
[0096] (1) Analysis of polymer compounds (1-1) Qualitative analysis of polymer compounds (a) OxyC 2-4 Analysis of alkylene units A crushed sample A is used. 150.0±0.1 mL of chloroform is added to 100.0±0.1 g of sample A, and the mixture is stirred at 20±5° C. for 16 hours to extract the polymer compound. The solid content is then removed by filtration. The polymer compound is identified by obtaining information from at least one of infrared spectroscopy, ultraviolet-visible absorption spectroscopy, NMR spectroscopy, LC-MS, and pyrolysis GC-MS for the chloroform solution in which the polymer compound obtained by extraction is dissolved or the polymer compound obtained by drying the chloroform solution.
[0097] The chloroform soluble matter is recovered by distilling off the chloroform under reduced pressure from the chloroform solution in which the polymer compound obtained by extraction is dissolved. The chloroform soluble matter is dissolved in deuterated chloroform and then subjected to the following conditions: 1 1H-NMR spectrum is measured. 1 From the H-NMR spectrum, a peak with a chemical shift in the range of 3.2 ppm to 3.8 ppm is confirmed. Also, from the peak in this range, oxy C 2-4 Identify the type of alkylene unit.
[0098] Equipment: AL400 nuclear magnetic resonance equipment manufactured by JEOL Ltd. Observation frequency: 395.88MHz Pulse width: 6.30μs Pulse repetition time: 74.1411 seconds Accumulation count: 32 Measurement temperature: room temperature (20~35℃) Standard: 7.24ppm Sample tube diameter: 5mm
[0099] 1 From the H-NMR spectrum, the integral value (V1) of the peaks present in the chemical shift range of 3.2 ppm to 3.8 ppm is calculated. In addition, for each of the hydrogen atoms of the -CH2- group and -CH< group bonded to the oxygen atom bonded to the terminal group of the polymer compound, 1 The sum (V2) of the integral values of the peaks in the H-NMR spectrum is calculated. Then, from V1 and V2, the percentage of V1 in the sum of V1 and V2 (=V1 / (V1+V2)×100(%)) is calculated.
[0100] In addition, in the qualitative analysis, 1 When calculating the integral value of a peak in a H-NMR spectrum, 1 In the H-NMR spectrum, two points without significant signals are determined so as to sandwich the corresponding peak, and each integral value is calculated using a straight line connecting these two points as a baseline. For example, for a peak that exists in a chemical shift range of 3.2 ppm to 3.8 ppm, a straight line connecting two points on the spectrum between 3.2 ppm and 3.8 ppm is used as the baseline. For example, for a peak that exists in a chemical shift range of more than 3.8 ppm to 4.0 ppm, a straight line connecting two points on the spectrum between 3.8 ppm and 4.0 ppm is used as the baseline.
[0101] (b) Analysis of hydrophobic groups in esterified products When the polymer compound is an ester of a hydroxy compound, a predetermined amount of the polymer compound obtained by drying the chloroform solution in which the polymer compound obtained by extraction is dissolved in (a) is collected, and an aqueous potassium hydroxide solution is added. This causes the ester to be saponified, producing a fatty acid potassium salt and a hydroxy compound. The aqueous potassium solution is added until the saponification is complete. The fatty acid potassium salt is converted to a fatty acid methyl ester by adding and mixing a solution of methanol and boron trifluoride to the resulting mixture. The resulting mixture is analyzed by pyrolysis GC-MS under the following conditions to identify the hydrophobic group contained in the ester. Analytical equipment: Shimadzu Corporation, high-performance general-purpose gas chromatogram GC-2014 Column: DEGS (diethylene glycol succinate) 2.1m Oven temperature: 180~120℃ Inlet temperature: 240℃ Detector temperature: 240℃ Carrier gas: He (flow rate: 50 mL / min) Injection volume: 1μL~2μL
[0102] (c) Analysis of hydrophobic groups in etherified products When the polymer compound is an etherified product of a hydroxy compound, a predetermined amount of the polymer compound obtained by drying the chloroform solution in which the polymer compound obtained by extraction is dissolved in (a) is collected and hydrogen iodide is added. This converts the organic group (the above-mentioned R 3 ) corresponding to the iodide (R 3 I) is generated and oxy C 2-4 Diiodo C corresponding to the alkylene unit 2-4 Alkanes are produced. The hydrogen iodide is converted to etherified iodide and diiodo C. 2-4 Add a sufficient amount of ether to complete the conversion to an alkane. The resulting mixture is analyzed by pyrolysis GC-MS under the same conditions as in (b) above to identify the hydrophobic group contained in the etherified product.
[0103] (1-2) Quantitative analysis of polymer compounds An appropriate amount of the above chloroform-soluble matter was dissolved in deuterated chloroform together with tetrachloroethane (TCE) whose mr(g) was measured to an accuracy of ±0.0001 g. 1 Measure the H-NMR spectrum. Calculate the integral value (Sa) of the peak present in the chemical shift range of 3.2 to 3.8 ppm and the integral value (Sr) of the peak derived from TCE, and calculate the mass-based content Cn (ppm) of the polymer compound in the negative electrode material from the following formula.
[0104] Cn=Sa / Sr×Nr / Na×Ma / Mr×mr / m×1000000 (In the formula, Ma is the molecular weight of a structure having a chemical shift peak in the range of 3.2 to 3.8 ppm (more specifically, oxy C 2-4 (molecular weight of alkylene unit), Na is the number of hydrogen atoms bonded to the carbon atoms of the main chain of the repeating structure. Nr and Mr are the number of hydrogen atoms contained in the molecule of the reference material and the molecular weight of the reference material, respectively, and m (g) is the mass of the negative electrode material used for extraction.) In addition, since the reference substance in this analysis is TCE, Nr=2, Mr=168, and m=100.
[0105] For example, when the polymer compound is polypropylene glycol, Ma is 58 and Na is 3. When the polymer compound is polyethylene glycol, Ma is 44 and Na is 4. In the case of a copolymer, Na and Ma are values obtained by averaging the Na value and Ma value of each monomer unit using the molar ratio (mol%) of each monomer unit contained in the repeating structure.
[0106] In addition, in the quantitative analysis, 1 The integral value of the peak in the H-NMR spectrum is determined using data processing software “ALICE” manufactured by JEOL Ltd.
[0107] (1-3) Mn measurement of polymer compounds Using the above chloroform solubles, GPC measurement of the polymer compound is carried out using the following apparatus under the following conditions. Separately, a calibration curve (calibration curve) is created from a plot of Mn of the standard substance versus elution time. Based on this calibration curve and the GPC measurement results of the polymer compound, the Mn of the polymer compound is calculated. However, esterified or etherified products may be in a decomposed state in the chloroform solubles.
[0108] Analysis system: 20A system (Shimadzu Corporation) Column: Two GPC KF-805L (Shodex) columns connected in series Column temperature: 30℃±1℃ Mobile phase: Tetrahydrofuran Flow rate: 1mL / min. Concentration: 0.20% by mass Injection volume: 10μL Standard substance: polyethylene glycol (Mn=2,000,000, 200,000, 20,000, 2,000, 200) Detector: Differential refractive index detector (Shodex RI-201H)
[0109] (2) Analysis of organic shrinkage inhibitors (2-1) Qualitative analysis of organic shrinkage inhibitors in negative electrode materials The ground sample A is immersed in a 1 mol / L aqueous solution of sodium hydroxide to extract the organic shrink-proofing agent. Next, insoluble components are removed from the extract by filtration, and the resulting solution is desalted, concentrated, and dried. Desalting is performed using a desalting column, by passing the solution through an ion exchange membrane, or by placing the solution in a dialysis tube and immersing it in distilled water. By drying this, a powder sample of the organic shrink-proofing agent (hereinafter referred to as sample B) is obtained.
[0110] The type of organic shrink-proofing agent is identified by combining information obtained from the following: infrared spectrum measured using sample B of the organic shrink-proofing agent obtained in this manner; ultraviolet-visible absorption spectrum measured using an ultraviolet-visible spectrometer after diluting sample B with distilled water or the like; NMR spectrum of a solution obtained by dissolving sample B in a specified solvent such as heavy water; or information obtained from pyrolysis GC-MS, which can provide information on the individual compounds that make up the substance.
[0111] (2-2) Quantitative determination of organic shrinkage inhibitor content in negative electrode material As in the above (2-1), the insoluble components are removed from the extract by filtration to obtain a solution. The ultraviolet-visible absorption spectrum of each solution obtained is measured. The content of the organic shrinkage inhibitor in the negative electrode material is determined using the intensity of the peak characteristic of each organic shrinkage inhibitor and a calibration curve prepared in advance.
[0112] In addition, when a lead-acid battery with an unknown content of organic shrink-proofing agent is obtained and the content of the organic shrink-proofing agent is measured, the structural formula of the organic shrink-proofing agent cannot be precisely specified, so that the same organic shrink-proofing agent cannot be used for the calibration curve. In this case, a calibration curve is created using the organic shrink-proofing agent extracted from the negative electrode of the battery and a separately available organic polymer that shows similar shapes in the ultraviolet-visible absorption spectrum, infrared spectroscopy spectrum, NMR spectrum, etc., and the content of the organic shrink-proofing agent is measured using the ultraviolet-visible absorption spectrum.
[0113] (3) Quantitative analysis of carbonaceous materials and barium sulfate Add 50 ml of 20% by mass nitric acid to 10 g of crushed sample A, heat for about 20 minutes, and dissolve the lead components as lead ions. Filter the resulting solution to separate solids such as carbonaceous materials and barium sulfate.
[0114] The obtained solid content is dispersed in water to obtain a dispersion liquid, and then a sieve is used to remove components other than the carbonaceous material and barium sulfate (e.g., reinforcing material) from the dispersion liquid. Next, the dispersion liquid is subjected to suction filtration using a membrane filter whose mass has been measured in advance, and the membrane filter together with the filtered sample is dried in a dryer at 110°C ± 5°C. The filtered sample is a mixed sample of the carbonaceous material and barium sulfate. The mass of the membrane filter is subtracted from the total mass of the mixed sample after drying (hereinafter referred to as sample C) and the membrane filter to measure the mass (Mm) of sample C. Then, sample C is placed in a crucible together with the membrane filter and incinerated at 1300°C or higher. The remaining residue is barium oxide. The mass of barium oxide is converted to the mass of barium sulfate to obtain the mass (MB) of barium sulfate. The mass of the carbonaceous material is calculated by subtracting the mass MB from the mass Mm.
[0115] [Positive plate] The positive electrode plate includes a positive electrode material and a positive electrode current collector. The positive electrode plate can be formed by applying or filling a positive electrode paste onto the positive electrode current collector, aging and drying to prepare an unformed positive electrode plate, and then forming the unformed positive electrode plate. The positive electrode paste is prepared, for example, by kneading lead powder, additives as necessary, water, and sulfuric acid (or an aqueous sulfuric acid solution). The unformed negative electrode plate may be aged at a temperature higher than room temperature and at a high humidity.
[0116] The formation can be carried out by immersing an electrode plate group including unformed positive plates in an electrolyte solution containing sulfuric acid in a battery container of a lead-acid battery and charging the electrode plate group in this state. However, the formation may also be carried out before assembling the lead-acid battery or the electrode plate group.
[0117] (Positive electrode current collector) The positive electrode current collector may be formed by casting lead (Pb) or a lead alloy, or may be formed by processing a lead sheet or a lead alloy sheet. Examples of the processing method include expanding and punching. It is preferable to use a lattice-shaped current collector as the positive electrode current collector because it is easy to support the positive electrode material.
[0118] The lead alloy used for the positive electrode current collector is preferably a Pb-Sb alloy, a Pb-Ca alloy, or a Pb-Ca-Sn alloy. The positive electrode current collector may have a surface layer. The surface layer and the inner layer of the positive electrode current collector may have different compositions. The surface layer may be formed on a part of the positive electrode current collector. The surface layer may be formed only on the lattice part, the edge part, or the frame part of the positive electrode current collector.
[0119] (Positive electrode material) The positive electrode material contains a positive electrode active material (lead dioxide or lead sulfate) that exhibits capacity through an oxidation-reduction reaction. The positive electrode material may contain an additive, if necessary.
[0120] (AGM separator) An AGM separator is disposed between the negative electrode plate and the positive electrode plate. The AGM separator is, for example, a nonwoven fabric formed from glass fibers in a sheet shape. The nonwoven fabric is a mat in which fibers are intertwined without being woven. The entire AGM separator may be formed from glass fibers, or the AGM separator may contain glass fibers as a main component. The AGM separator may contain components other than glass fibers, such as organic fibers, acid-resistant inorganic powder, and polymers as binders. When the main component of the AGM separator is glass fiber, the content of glass fiber may be, for example, 60% by mass or more, or 70% by mass or more.
[0121] The average fiber diameter of the glass fibers may be, for example, 0.1 μm or more and 30 μm or less, or 0.5 μm or more and 15 μm or less. The average fiber diameter of the glass fibers may be calculated by determining the maximum diameter of any cross section perpendicular to the length direction of any 100 fibers and averaging the values of the 100 fibers.
[0122] (Organic Fiber) The AGM separator may contain organic fibers. Polymer compounds are more easily adsorbed by organic fibers than hydrophilic glass fibers containing hydroxyl groups (-OH). Therefore, the polymer compounds eluted from the negative electrode material into the electrolyte tend to preferentially adsorb to the organic fibers and remain in the AGM separator. As a result, the polymer compounds eluted into the electrolyte are less likely to reach the positive electrode plate. The AGM separator may contain organic fibers in an amount of, for example, 5% by mass or more and 20% by mass or less.
[0123] The organic fiber content of the AGM separator can be measured by igniting the AGM separator in a muffle furnace and measuring the mass difference before and after. The organic fibers are burned away by igniting the AGM separator in a muffle furnace. Therefore, the decrease in mass can be considered to be the mass of the organic fibers.
[0124] The organic fiber may be, for example, a resin fiber, a pulp fiber, etc. Resins constituting the resin fiber include, but are not limited to, acrylic resins containing polyacrylonitrile units, acrylic acid units, methacrylic acid units, acrylic acid ester units, methacrylic acid ester units, etc., polyester resins such as polyethylene terephthalate, and polyolefin resins such as polyethylene and polypropylene.
[0125] The average fiber diameter of the organic fibers may be, for example, 1 μm or more and 15 μm or less, or 5 μm or more and 10 μm or less. The average fiber diameter of the organic fibers may be calculated by determining the maximum diameter of any cross section perpendicular to the length direction of any 100 fibers and averaging the values of the 100 fibers.
[0126] (ceramic powder) The AGM separator may further include a ceramic powder, such as silica powder.
[0127] [Electrolyte] The electrolyte is an aqueous solution containing sulfuric acid, which may be gelled as necessary. The electrolyte may contain the above-mentioned polymer compound.
[0128] The electrolytic solution may contain cations (e.g., metal cations) and / or anions (e.g., anions other than sulfate anions (e.g., phosphate ions)) as necessary. Examples of metal cations include at least one selected from the group consisting of Na ions, Li ions, Mg ions, and Al ions.
[0129] The specific gravity of the electrolyte in a fully charged lead-acid battery at 20° C. is, for example, 1.20 or more, and may be 1.25 or more. The specific gravity of the electrolyte at 20° C. is 1.35 or less, and preferably 1.32 or less.
[0130] The specific gravity of the electrolyte at 20° C. may be 1.20 or more and 1.35 or less, 1.20 or more and 1.32 or less, 1.25 or more and 1.35 or less, or 1.25 or more and 1.32 or less.
[0131] Fig. 1 is a cross-sectional view showing a schematic structure of an example of a valve-regulated lead-acid battery. In Fig. 1, the lead-acid battery 1 includes a battery case 10 that contains a plate group 11 and an electrolyte (not shown). The upper opening of the battery case 10 is sealed with a lid 12A. The plate group 11 is formed by stacking a plurality of negative electrode plates 2 and positive electrode plates 3 with separators 4 interposed therebetween.
[0132] An upwardly protruding current collecting lug (not shown) is provided on the upper portion of each of the plurality of negative electrode plates 2. An upwardly protruding current collecting lug (not shown) is also provided on the upper portion of each of the plurality of positive electrode plates 3. The lugs of the negative electrode plates 2 are connected and integrated with each other by a negative electrode strap (not shown). Similarly, the lugs of the positive electrode plates 3 are connected and integrated with each other by a positive electrode strap (not shown). The negative electrode strap is connected to a negative electrode pole (not shown) that serves as an external terminal, and the positive electrode strap is connected to a positive electrode pole (not shown) that serves as an external terminal.
[0133] The battery container 10 is divided into multiple (three in the illustrated example) mutually independent cell chambers 10R, and each cell chamber 10R houses one electrode plate group 11. The lid 12 is provided with an independent exhaust valve 13 for each cell chamber 10R. When the internal pressure of the cell chamber 10R exceeds a predetermined upper limit, the exhaust valve 13 opens, directly releasing gas from the cell chamber 10R to the outside. When the internal pressure of the cell chamber 10R is below the upper limit, oxygen generated in the positive electrode plate 3 is reduced in the negative electrode plate 2 in the same cell chamber 10R to produce water.
[0134] The structure of the valve-regulated lead-acid battery is not limited to the above. For example, although an individual cell exhaust type is shown in Fig. 1, the battery may be of a collective exhaust type in which the cover has a collective exhaust chamber communicating with each cell chamber, and the collective exhaust chamber has a smaller number of exhaust valves than the number of cell chambers (for example, one).
[0135] In this specification, the amount of electrolyte loss and the capacity retention rate at high rate discharge are evaluated by a float life test according to the following procedure: The test battery used for the evaluation has a rated voltage of 2V / cell and a rated 10-hour rate capacity of 50Ah.
[0136] <Float life test> The batteries were placed in a water tank at 60°C ±3°C and float charged at a constant voltage of 2.23V / cell. Every 30 days of the month, the capacity was measured at high rate discharge and the battery mass was measured under the following conditions.
[0137] (a) Amount of liquid reduction The amount of electrolyte loss is calculated from the amount of loss in the battery mass as follows: Liquid reduction amount (%)=100×(Wa-Wb) / Wa Wa: Battery mass before testing Wb: Battery mass after a specified period of testing
[0138] (b) Capacity retention rate at high rate discharge A high-rate discharge at 150A (3C (1C means the current (A) of the numerical value (Ah) listed as the rated capacity)) is carried out to a discharge cut-off voltage of 1.0V / cell, and the initial capacity is calculated. After that, the battery is charged to 90% of the discharge capacity at 10A (0.2C), and subsequently charged to 45% of the discharge capacity (135% in total) at 2.5A (0.05C). Float charging is then continued at a constant voltage of 2.23V / cell. Then, every 30 days, the capacity is measured at the same high-rate discharge, and the ratio of the obtained capacity to the initial capacity is calculated as a percentage.
[0139] The valve regulated lead acid battery according to the present invention will be described below.
[0140] (1) A valve-regulated lead-acid battery, The battery includes an electrode plate group, an electrolyte, and a battery case that contains the electrode plate group and the electrolyte, The electrode plate group includes a positive electrode plate, a negative electrode plate, and an AGM separator interposed between the positive electrode plate and the negative electrode plate, A pressure applied to the electrode plate group in the battery container in a stacking direction of the positive electrode plates and the negative electrode plates is 10 kPa or more and 40 kPa or less, The density of the AGM separator when a compressive force of 20 kPa is applied in the thickness direction is 0.14 g / cm 3 More than 0.20g / cm 3 is as follows: The negative electrode plate includes a negative electrode material, The negative electrode material includes a polymer compound, The polymer compound is measured using deuterated chloroform as a solvent. 1 A valve-regulated lead-acid battery having a peak in the range of 3.2 ppm or more and 3.8 ppm or less in the chemical shift of the H-NMR spectrum.
[0141] (2) The polymer compound is oxyC 2-4 The valve-regulated lead-acid battery according to (1) above, having a repeating structure of alkylene units.
[0142] (3) A valve-regulated lead-acid battery, The battery includes an electrode plate group, an electrolyte, and a battery case that contains the electrode plate group and the electrolyte, The electrode plate group includes a positive electrode plate, a negative electrode plate, and an AGM separator interposed between the positive electrode plate and the negative electrode plate, A pressure applied to the electrode plate group in the battery container in a stacking direction of the positive electrode plates and the negative electrode plates is 10 kPa or more and 40 kPa or less, The density of the AGM separator when a compressive force of 20 kPa is applied in the thickness direction is 0.14 g / cm 3 More than 0.20g / cm 3 is as follows: The negative electrode plate includes a negative electrode material, The negative electrode material includes a polymer compound, The polymer compound is oxyC 2-4 A valve-regulated lead-acid battery having a repeating structure of alkylene units.
[0143] (4) The valve regulated lead-acid battery according to (2) or (3) above, wherein the polymer compound includes at least one selected from the group consisting of a hydroxy compound having the repeating structure, an etherified product of the hydroxy compound, and an esterified product of the hydroxy compound.
[0144] (5) The hydroxy compound is polyC 2-4 Alkylene glycol, oxy C 2-4 A copolymer containing a repeating structure of an alkylene unit, and a polyol, polyC 2-4 The valve regulated lead-acid battery according to (4) above, wherein the compound is at least one selected from the group consisting of alkylene oxide adducts.
[0145] (6) The oxy C 2-4 The valve regulated lead-acid battery according to any one of the above (2) to (5), wherein the alkylene unit is an oxypropylene unit.
[0146] (7) The oxy C 2-4 The valve regulated lead-acid battery according to any one of the above (2) to (5), wherein the alkylene unit is an oxyethylene unit.
[0147] (8) the polymeric compound comprises an oxygen atom bonded to a terminal group and a -CH- group and / or a -CH< group bonded to the oxygen atom; The above 1 The valve-regulated lead-acid battery according to any one of the above (1) to (8), wherein in a H-NMR spectrum, a ratio of an integral value of the peak to a total of an integral value of the peak, an integral value of a peak of a hydrogen atom of the -CH2- group, and an integral value of a peak of a hydrogen atom of the -CH< group is 85% or more.
[0148] (9) The polymer compound has one or more hydrophobic groups, The valve regulated lead-acid battery according to any one of the above (1) to (8), wherein at least one of the hydrophobic groups is a long-chain aliphatic hydrocarbon group having 8 or more carbon atoms.
[0149] (10) The valve regulated lead-acid battery according to any one of (1) to (9) above, wherein the content of the polymer compound in the negative electrode material is in the range of 30 ppm to 500 ppm by mass.
[0150] (11) The valve regulated lead-acid battery according to any one of (1) to (10) above, wherein the polymer compound includes a compound having a number average molecular weight of 10,000 or less.
[0151] (12) The valve regulated lead-acid battery according to any one of (1) to (11) above, wherein the polymer compound includes a compound having a number average molecular weight of 500 or more.
[0152] (13) The valve regulated lead-acid battery according to any one of (1) to (12) above, wherein the AGM separator contains organic fibers in an amount of 5% by mass or more and 20% by mass or less.
[0153] [Example] The present invention will be specifically described below based on examples and comparative examples, but the present invention is not limited to the following examples.
[0154] 《Lead acid batteries E1~E6, R1》 (1) Preparation of lead-acid batteries (a) Preparation of the negative electrode plate The raw material lead powder, lignin as an organic shrinkage inhibitor, barium sulfate, carbon black, and polyethylene glycol (PEG) as a polymer compound are mixed with an appropriate amount of sulfuric acid aqueous solution to obtain a negative electrode paste. The components are mixed so that the content of the polymer compound in the negative electrode material obtained by the above-mentioned procedure is the value shown in Tables 1 and 2, the content of the organic shrinkage inhibitor is 0.1 mass%, the content of the barium sulfate is 0.4 mass%, and the content of the carbon black is 0.2 mass%. The density of the negative electrode material contained in the lead-acid battery in a fully charged state after chemical formation is 3.6 g / cm 3 The concentration and amount of the sulfuric acid aqueous solution are adjusted so that the negative electrode paste is filled into the mesh of an expanded lattice made of a Pb-Ca-Sn alloy, and the negative electrode paste is aged and dried to obtain an unformed negative electrode plate.
[0155] The number average molecular weight Mn of the polymer compound (polyethylene glycol (PEG)) measured by the above-mentioned procedure was 500. 1 In the H-NMR spectrum, a peak derived from -CH2- of the oxyethylene unit is observed in the chemical shift range of 3.2 ppm to 3.8 ppm. 1 In the H-NMR spectrum, the percentage of the integral value of the peak derived from -CH2- of the oxyethylene unit to the sum of the integral value of this peak and the integral value of the peaks of the hydrogen atoms of the -CH2- groups and / or -CH< groups bonded to the oxygen atoms bonded to the terminal groups is 99%.
[0156] (b) Preparation of the positive electrode plate The raw lead powder is mixed with an aqueous sulfuric acid solution to obtain a positive electrode paste, which is then filled into the mesh of an expanded lattice made of a Pb-Ca-Sn alloy, aged and dried to obtain an unformed positive electrode plate.
[0157] (c) Preparation of AGM separator The 20 kPa density obtained by the above method is 0.14 g / cm 3An AGM separator having a thickness t (cm) of 0.25 cm (i.e., 2.5 mm) per sheet, as determined by the method described above, is prepared. 90% by mass of the AGM separator is glass fiber (average fiber diameter 0.8 μm) and 10% by mass is organic fiber.
[0158] (d) Preparation of test battery The test battery has a rated voltage of 2V and a rated 10-hour rate capacity of 50Ah. The plate group of the test battery is composed of five positive plates and six negative plates. The positive and negative plates are alternately stacked with AGM separators in between to form a plate group. The plate group is placed in a polypropylene container together with an electrolyte (aqueous sulfuric acid solution) and chemically treated in the container to produce a valve-regulated lead-acid battery. The pressure required by the method described above is 10kPa. The specific gravity of the electrolyte in a fully charged lead-acid battery at 20°C is 1.28.
[0159] (2) Float life test A float life test was carried out using the method described above, and the amount of electrolyte loss and the capacity retention rate at high rate discharge were determined every month. The results of the electrolyte loss are shown in Table 1. The capacity retention rate at high rate discharge (HR capacity retention rate) is shown in Table 2.
[0160] [Table 1]
[0161] From Table 1, it can be seen that when the negative electrode material contains polyethylene glycol (PEG) as a polymer compound, the greater the PEG content in the negative electrode material, the greater the effect of suppressing the loss of electrolyte. It can also be seen that when the PEG content is 30 ppm or more, the suppression of the loss of electrolyte is more remarkable.
[0162] [Table 2]
[0163] From Table 2, when the negative electrode material contains polyethylene glycol (PEG) as a polymer compound, the pressure of the electrode assembly must be 10 kPa or more and 40 kPa or less, and the 20 kPa density of the AGM separator must be 0.14 g / cm 3 More than 0.20g / cm 3 It can be seen that the decrease in the capacity retention rate during high-rate discharge is suppressed by setting the PEG content at or below 30 ppm. It can also be seen that the capacity retention rate during high-rate discharge is improved more significantly when the PEG content is 30 ppm or more and 600 ppm or less.
[0164] 《Lead acid battery E7~E9, R2》 A valve-regulated lead-acid battery is prepared in the same manner as in Example E3 (PEG content 80 ppm), except that the pressure obtained by the above-mentioned method is set to the values shown in Tables 3 and 4, and a float life test is carried out. The results of the amount of electrolyte loss are shown in Table 3. The capacity retention rate at high rate discharge is shown in Table 4.
[0165] [Table 3]
[0166] From Table 3, it can be seen that even when the negative electrode material contains polyethylene glycol (PEG) as a polymer compound, the effect of suppressing the loss of electrolyte is small when the pressure applied to the electrode assembly is less than 10 kPa. On the other hand, when the pressure applied to the electrode assembly is 10 kPa or more, the effect of suppressing the loss of electrolyte is remarkable.
[0167] [Table 4]
[0168] From Tables 4 and 2, it can be seen that regardless of whether or not the negative electrode material contains polyethylene glycol (PEG) as a polymer compound, when the pressure applied to the plate group is less than 10 kPa, there is almost no effect in improving the capacity retention rate during high-rate discharge. On the other hand, when the pressure applied to the plate group is 10 kPa or more, the greater the pressure, the more the capacity retention rate during high-rate discharge improves.
[0169] 《Lead acid battery R3~R7》 A valve-regulated lead-acid battery is prepared in the same manner as in Comparative Example R1 (PEG content 0 ppm), except that the pressure obtained by the above-mentioned method is set to the values shown in Tables 3 and 4, and a float life test is carried out. The results of the amount of electrolyte loss are shown in Table 5. The capacity retention rate at high rate discharge is shown in Table 6.
[0170] [Table 5]
[0171] From Table 5, it can be seen that when the negative electrode material does not contain a polymer compound, the loss of liquid cannot be suppressed regardless of the pressure applied to the electrode plate group.
[0172] [Table 6]
[0173] From Table 6, it can be seen that when the negative electrode material does not contain a polymer compound, there is almost no improvement in the capacity retention rate during high-rate discharge, regardless of the pressure applied to the electrode plate assembly.
[0174] 《Lead acid battery E10~12, R8~9》 Except for the 20 kPa density of the AGM separator obtained by the above-mentioned method being the value shown in Tables 7 and 8, a valve-regulated lead-acid battery is prepared in the same manner as in Example E3 (PEG content 80 ppm), and a float life test is carried out. The results of the amount of liquid loss are shown in Table 7. The capacity retention rate at high rate discharge is shown in Table 8.
[0175] [Table 7]
[0176] From Table 7, the 20 kPa density of the AGM separator is 0.2 g / cm 3 Above this value, the effect of suppressing the loss of liquid becomes smaller. Therefore, the 20 kPa density of the AGM separator is 0.2 g / cm 3 It is necessary to do the following.
[0177] [Table 8]
[0178] From Table 8, the 20 kPa density of the AGM separator is 0.14 g / cm 3 It can be seen that the capacity retention rate during high-rate discharge cannot be improved when the 20 kPa density of the AGM separator is less than 0.2 g / cm 3 Therefore, the 20 kPa density of the AGM separator is 0.14 g / cm. 3 More than 0.2g / cm 3 It is necessary to do the following.
[0179] 《Lead acid battery E13~17》 A valve-regulated lead-acid battery is prepared in the same manner as in Example E3 (PEG content 80 ppm), except that the organic fiber content determined by the above-mentioned method is set to the value shown in Tables 9 and 10, and a float life test is carried out. The results of the amount of electrolyte loss are shown in Table 9. The capacity retention rate at high rate discharge is shown in Table 10.
[0180] [Table 9]
[0181] From Table 9, it can be seen that when the AGM separator contains organic fibers, the content is preferably 20 mass % or less.
[0182] [Table 10]
[0183] Table 9 shows that when organic fibers are contained in the AGM separator, it is desirable for the content to be 5% by mass or more, and that up to 20% by mass, a higher organic fiber content is more advantageous in improving the capacity retention rate during high-rate discharge.
[0184] 《Lead acid battery E18~23, R10》 Except for changing the polymer compound from PEG to polyethylene glycol oleate, an ester of PEG, a valve-regulated lead-acid battery was fabricated and a float life test was carried out in the same manner as in Tables 1 and 2. The results of the amount of electrolyte loss are shown in Table 11. The capacity retention rate during high-rate discharge is shown in Table 12.
[0185] [Table 11]
[0186] [Table 12]
[0187] 《Lead acid battery E24~29, R11》 Except for changing the polymer compound from PEG to polyethylene glycol dilaurate, an ester of PEG, a valve-regulated lead-acid battery was fabricated and a float life test was carried out in the same manner as in Tables 1 and 2. The results of the amount of electrolyte loss are shown in Table 13. The capacity retention rate at high rate discharge is shown in Table 14.
[0188] [Table 13]
[0189] [Table 14]
[0190] 《Lead acid battery E30~35, R12》 Except for changing the polymer compound from PEG to polyethylene glycol distearate, an ester of PEG, a valve-regulated lead-acid battery was fabricated and a float life test was carried out in the same manner as in Tables 1 and 2. The results of the amount of electrolyte loss are shown in Table 15. The capacity retention rate during high-rate discharge is shown in Table 16.
[0191] [Table 15]
[0192] [Table 16]
[0193] 《Lead acid battery E36~41, R13》 Except for changing the polymer compound from PEG to polyethylene glycol dioleate, an ester of PEG, a valve-regulated lead-acid battery was fabricated and a float life test was carried out in the same manner as in Tables 1 and 2. The results of the amount of electrolyte loss are shown in Table 17. The capacity retention rate at high rate discharge is shown in Table 18.
[0194] [Table 17]
[0195] [Table 18]
[0196] The results in Tables 11 to 18 show that, similarly to the case where polyethylene glycol (PEG) was used as the polymer compound, when an esterified product of PEG was used, the pressure applied to the electrode group was set to 10 kPa or more and 40 kPa or less, and the 20 kPa density of the AGM separator was set to 0.14 g / cm. 3 More than 0.20g / cm 3 It can be seen that by setting the above, the decrease in the capacity retention rate during high-rate discharge can be suppressed while suppressing the loss of the electrolyte. [Industrial Applicability]
[0197] The valve regulated lead-acid battery according to the present invention is suitable as a stationary valve regulated lead-acid battery such as an uninterruptible power supply (UPS), but its use is not particularly limited. [Explanation of symbols]
[0198] 1: Valve-regulated lead-acid battery 2: Negative plate 3: Positive plate 4: Separator 11: Plate group 10: Battery case 10R: Cell Room 12: Lid 13: Exhaust valve
Claims
1. The battery includes an electrode plate group, an electrolyte, and a battery case that contains the electrode plate group and the electrolyte, The electrode plate group includes a positive electrode plate, a negative electrode plate, and an AGM separator interposed between the positive electrode plate and the negative electrode plate, A pressure applied to the electrode plate group in the battery container in a stacking direction of the positive electrode plates and the negative electrode plates is 10 kPa or more and 40 kPa or less, The density of the AGM separator when a compressive force of 20 kPa is applied in the thickness direction is 0.14 g / cm 3 Above, 0.20g / cm 3 is as follows: The negative electrode plate includes a negative electrode material, The negative electrode material includes a polymer compound, The polymer compound is measured using deuterated chloroform as a solvent. 1 The present invention relates to a valve-regulated lead-acid battery having a peak attributable to a repeating structure of oxy-C 2-4 alkylene units in the range of 3.2 ppm to 3.8 ppm in the chemical shift of a 1 H-NMR spectrum.
2. The battery includes an electrode plate group, an electrolyte, and a battery case that contains the electrode plate group and the electrolyte, The electrode plate group includes a positive electrode plate, a negative electrode plate, and an AGM separator interposed between the positive electrode plate and the negative electrode plate, A pressure applied to the electrode plate group in the battery container in a stacking direction of the positive electrode plates and the negative electrode plates is 10 kPa or more and 40 kPa or less, The density of the AGM separator when a compressive force of 20 kPa is applied in the thickness direction is 0.14 g / cm 3 Above, 0.20g / cm 3 is as follows: The negative electrode plate includes a negative electrode material, The negative electrode material includes a polymer compound, The polymer compound is oxyC 2-4 A valve-regulated lead-acid battery having a repeating structure of alkylene units.
3. 3. The valve regulated lead-acid battery according to claim 1, wherein the polymer compound comprises at least one selected from the group consisting of a hydroxy compound having the repeating structure, an etherified product of the hydroxy compound, and an esterified product of the hydroxy compound.
4. The hydroxy compound is polyC 2-4 Alkylene glycol, oxy C 2-4 A copolymer containing a repeating structure of an alkylene unit and a polyol, polyC 2-4 4. The valve regulated lead-acid battery according to claim 3, wherein the compound is at least one selected from the group consisting of alkylene oxide adducts.
5. The oxy C 2-4 The valve regulated lead-acid battery according to any one of claims 1 to 4, wherein the alkylene unit is an oxypropylene unit.
6. The oxy C 2-4 The valve-regulated lead-acid battery according to any one of claims 1 to 4, wherein the alkylene unit is an oxyethylene unit.
7. The polymer compound has an oxygen atom bonded to a terminal group and a —CH 2 - and / or -CH< groups, The above 1 In the H-NMR spectrum, the integral value of the peak and the integral value of the -CH 2 2. The valve regulated lead-acid battery according to claim 1, wherein a ratio of the integral value of the peak of the hydrogen atom of the - group to the integral value of the peak of the hydrogen atom of the -CH< group in the total is 85% or more.
8. The polymer compound has one or more hydrophobic groups, The valve regulated lead-acid battery according to any one of claims 1 to 7, wherein at least one of the hydrophobic groups is a long-chain aliphatic hydrocarbon group having 8 or more carbon atoms.
9. The valve regulated lead-acid battery according to any one of claims 1 to 8, wherein the content of the polymer compound in the negative electrode material is in the range of 30 ppm to 500 ppm by mass.
10. The regulated valve lead-acid battery according to any one of claims 1 to 9, wherein the polymer compound includes a compound having a number average molecular weight of 10,000 or less.
11. The regulated valve lead-acid battery according to any one of claims 1 to 10, wherein the polymer compound includes a compound having a number average molecular weight of 400 or more.
12. The regulated valve lead-acid battery according to any one of claims 1 to 11, wherein the AGM separator contains organic fibers in a content of 5 mass% or more and 20 mass% or less.
Citation Information
Patent Citations
Namarichikudenchoinkyokuban
JP1976047237A
Manufacture of electrode for lead storage battery
JP1983019863A
Lead-acid battery
JP1985182662A
Sealed storage battery
JP1994283152A
Sealed lead-acid battery
JP1996203490A